METHODS OF STATISTICAL CONTROL OF QUALITY IN THE MANUFACTURE OF VINYL'S WALLPAPERS ON PAPER BASIS [Text] - Bogdanova, V.A.; Zhegera, K. V.; Zharylgapov, S. M.; Жарылгапов, С. М. (Science and education№1, 2018)
The article provides information about the types of control exercised in the production process. Since the largest number of marriage arises in the production process, we reviewed statistical methods that are implemented when carrying out operational control. In detail considered the construction of the control X-S-cards.В статье представлена информация о типах контроля, осуществляемых в процессе производства. Поскольку наибольшее количество браков возникает в производственном процессе, мы рассмотрели статистические методы, которые реализуются при осуществлении оперативного контроля. Подробно рассмотрено строительство управляющих X-S-карт.
Keywords: рк; отечественное издание; научный журнал; периодическое издание; браки в производстве; контроль производства